Pengaruh Permainan Tradisional Bola Bekel Terhadap Perkembangan Motorik Halus Anak - Annisa Herlida Sari; Dyah Ageng Pramesty Koenarso; Ayu Fajarwati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Fine motor skills refer to movements involving small muscle groups that require coordination between the eyes and hands. These skills develop through practice, learning experiences, and the maturation of motor functions. This study aimed to determine the effect of the traditional bekel ball game on the fine motor development of children aged 5–6 years. The study employed a quasi-experimental design involving 40 children in Group B at TK Ma'arif Lampung Timur, consisting of an experimental group and a control group. Data were collected using a fine motor development observation sheet and analyzed through paired sample t-tests and independent sample t-tests using SPSS version 16. The results revealed a significant effect of the traditional bekel ball game on children's fine motor development, with a significance value of 0.000 < 0.05. The average score of fine motor development in the experimental group increased from 65.50 to 80.50, representing an improvement of 22.90%. These findings indicate that the traditional bekel ball game is effective in stimulating fine motor development among early childhood learners. Therefore, traditional games can serve as an alternative learning medium to support children's fine motor development while preserving local cultural heritage